2015
DOI: 10.1177/2050312115598872
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy collected medication histories in an observation unit

Abstract: Background:Clear processes to facilitate medication reconciliation in a hospital setting are still undefined. The observation unit allows for a high patient turnover rate, where obtaining accurate medication histories is critical.Objectives:The objective of this study was to assess the ability of pharmacists and student pharmacists to identify discrepancies in medication histories obtained at triage in observation patients.Methods:Pharmacists and student pharmacists obtained a medication history for each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…14,16 Similarly, several of the studies had greater than 75% of patients identified as having an inaccurate medication history (Padiyara 75%, Lubowski et al 75%, Procopio et al 76%, ours 96%). 13,16,18 Study by Mersfelder and Bickel stated that 67% of patient charts had a medication or dosage omitted but did not include clarifications for directions or frequency in this and therefore was lower than the other stated studies. 15 A high number of patients required additional pharmacy intervention of contacting their outpatient pharmacy to obtain a recent medication list (Padiyara 68%, ours 79%, Mersfelder and Bickel 99%).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…14,16 Similarly, several of the studies had greater than 75% of patients identified as having an inaccurate medication history (Padiyara 75%, Lubowski et al 75%, Procopio et al 76%, ours 96%). 13,16,18 Study by Mersfelder and Bickel stated that 67% of patient charts had a medication or dosage omitted but did not include clarifications for directions or frequency in this and therefore was lower than the other stated studies. 15 A high number of patients required additional pharmacy intervention of contacting their outpatient pharmacy to obtain a recent medication list (Padiyara 68%, ours 79%, Mersfelder and Bickel 99%).…”
Section: Discussionmentioning
confidence: 87%
“…8 We identified 7 studies that describe the benefit of student pharmacist-obtained medication histories that have similarities in student training required and in the general patient interview process. [13][14][15][16][17][18][19] Similar to our practice site, all of the previously published studies were at institutions without pharmacy services that were established in obtaining medication histories. [13][14][15][16][17][18][19] Some similarities and differences existed between our results and those previously published when looking at patient types and intervention rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Additionally, Procopio et al found that pharmacists and pharmacy students identified an average of 2.9 medication discrepancies per patient among medication histories completed by nursing. 13 Recently, our 230-bed community hospital expanded pharmacy-led medication histories by allocating 2 full-time equivalents (FTEs) for pharmacy technicians and 0.8 FTEs for student pharmacist interns dedicated to completing medication histories. In this model, clinical pharmacists are occasionally called upon to complete complex histories or when a timely history completion is important and the designated technician or intern is not readily available.…”
Section: Introductionmentioning
confidence: 99%